JAMUR POLYPORALES DI TWA SURANADI LOMBOK BARAT - Sulastri, Meilinda Pahriana; Basri, Hasan (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2020)
Background: Mushrooms are a member of the kingdom of fungi, which has a high level of diversity in Indonesia. In general, fungi will grow in humid environmental conditions, especially during the rainy season on weathered wood, litter and trees. Macro fungi are fungi that form fruiting bodies and can be observed without using a microscope. Macro fungi generally consist of members of the Ascomycota and Basidomycota groups. This study aims to determine which mushrooms are included in the Polyporales order that grows in TWA Suranadi Methods: This research is descriptive exploratory by exploring and describing the macrophages found in TWA Suranadi. Sampling was carried out by the cruise method (Cruise Method). Identification is done by matching observational data in the form of morphological characteristics and environmental conditions using reference books and various scientific journals on macrofungal species. Results: The results showed that there were 7 species from 2 fungal families of the Polyporales order, namely: Trametes sp., Microporus sp. 1, Microporus sp. 2, Polyporus sp. 1, Polyporus sp. 2, Datronia sp. and Ganoderma sp. Conclusion: Based on the identification results, 2 families and 8 species were found belonging to the Polyporales order in TWA Suranadi, namely Trametes sp., Microporus sp. 1, Microporus sp. 2, Polyporus sp. 1, Polyporus sp. 2, Datronia sp., and Ganoderma sp.